Interrupting the silence: A critical discourse analysis of a pilot seminar on racism, intersectionality, and white privilege - Putman, Angela Lynn (ProQuest Dissertations & Theses, 2014)
This dissertation is based on the design and implementation of a pilot seminar for college undergraduates on the topics of racism, intersectionality, and white privilege. Utilizing Critical Communication Pedagogy as a theoretical and methodological approach, the author discusses the learning competencies, activities, and achieved learning outcomes related to the pilot seminar. Next, the author analyzes participants' discourse that emerged through seminar surveys, recordings of seminar activities, and observations. The author then analyzes the first research question, related to participants' negotiated constructions of racism, intersectionality, and white privilege and examines how these constructions did/did not reflect change throughout the seminar process. A number of ideological discourses emerged through participants' discourse before, during, and after the seminar and these discourses are also analyzed using a Critical Discourse Analysis approach. The author then discusses findings from the study that include participants' subject positioning within the discourse, the implications of ideological discourses that perpetuate the pervasiveness of whiteness and white privilege, and how these discourses reinforce social practices that reify hierarchies, power relations, and status positionings.